2007
DOI: 10.1063/1.2724740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic polarons on the magnetic, magnetocaloric, and magnetoresistance properties of the intermetallic compound HoNiAl

Abstract: The effect of distributed exchange parameters on magnetocaloric refrigeration capacity in amorphous and nanocomposite materials J. Appl. Phys. 111, 07A334 (2012) Particle size dependent hysteresis loss in La0.7Ce0.3Fe11.6Si1.4C0.2 firstorder systems Appl. Phys. Lett. 100, 072403 (2012) Magnetocaloric effect and refrigerant capacity in 0.44, 0.46 The magnetic, magnetocaloric, and magnetoresistive properties of the polycrystalline compound HoNiAl have been studied. The temperature variations of magnetizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 23 publications
9
45
0
1
Order By: Relevance
“…There may be a contribution from the complex magnetic structure as well, which causes the thermomagnetic irreversibility. 28,29 In Gd 2 Ni 2 Sn, the thermomagnetic irreversibility is found to be very small, which is due to the weak magnetic anisotropy associated with Gd 3+ ion. Since the domain wall pinning effect is quite prominent in materials with large magnetic anisotropy, negligible thermomagnetic irreversibility seen in Gd 2 Ni 2 Sn implies that at least in this compound, the domain wall pinning is the dominant factor in contributing the thermomagnetic irreversibility.…”
Section: Resultsmentioning
confidence: 97%
“…There may be a contribution from the complex magnetic structure as well, which causes the thermomagnetic irreversibility. 28,29 In Gd 2 Ni 2 Sn, the thermomagnetic irreversibility is found to be very small, which is due to the weak magnetic anisotropy associated with Gd 3+ ion. Since the domain wall pinning effect is quite prominent in materials with large magnetic anisotropy, negligible thermomagnetic irreversibility seen in Gd 2 Ni 2 Sn implies that at least in this compound, the domain wall pinning is the dominant factor in contributing the thermomagnetic irreversibility.…”
Section: Resultsmentioning
confidence: 97%
“…It has been reported that compounds of RNiAl series show µeff. higher than the theoretical value, which may arise due to polarization of 3d moment in Ni, and termed as magnetic polaronic effect, which is also responsible for some unusual magnetic properties in these compounds [195,196]. Most of the compounds of RNiAl series are metamagnetic in nature [195,196,197].…”
Section: Rnix Compoundsmentioning
confidence: 98%
“…It has been reported that the polaronic effect increases the resistivity of compound due to strong confinement of conduction electrons. On the application of magnetic field, size of polarons grow, coalesce, which causes the delocalization of conduction electrons and results in large MR [196]. YbNiAl shows logarithmic increase of resistivity by 25 % in the temperature between 100 to 10 K, which indicates heavy fermion behavior in this compound [190].…”
Section: Magneto-transport Propertiesmentioning
confidence: 99%
See 2 more Smart Citations